2014
DOI: 10.1523/jneurosci.2658-13.2014
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Fluctuations in Sustained Attention and Distractor Processing

Abstract: Although sustaining a moderate level of attention is critical in daily life, evidence suggests that attention is not deployed consistently, but rather fluctuates from moment to moment between optimal and suboptimal states. To better characterize these states in humans, the present study uses a gradual-onset continuous performance task with irrelevant background distractors to explore the relationship among behavioral fluctuations, brain activity, and, in particular, the processing of visual distractors. Using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
120
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(144 citation statements)
references
References 24 publications
16
120
0
1
Order By: Relevance
“…We focused on reaction time (RT) variability in the 30-s prerating period (except where indicated) because relative to shorter prerating time windows, we could use more samples to calculate RT metrics (23 trials) and acknowledge uncertainty in the duration of preprobe periods to which participants' thought-probe responses referred (but results from shorter prerating periods were largely similar; Table S2). For consistency with previous studies on the DMN and RT variability (19,20), we report our main analyses based on RT variance (absolute deviance from the mean) across trials preceding thought probes, but we also report results with RT coefficient of variation (CoV).…”
Section: Resultsmentioning
confidence: 84%
See 3 more Smart Citations
“…We focused on reaction time (RT) variability in the 30-s prerating period (except where indicated) because relative to shorter prerating time windows, we could use more samples to calculate RT metrics (23 trials) and acknowledge uncertainty in the duration of preprobe periods to which participants' thought-probe responses referred (but results from shorter prerating periods were largely similar; Table S2). For consistency with previous studies on the DMN and RT variability (19,20), we report our main analyses based on RT variance (absolute deviance from the mean) across trials preceding thought probes, but we also report results with RT coefficient of variation (CoV).…”
Section: Resultsmentioning
confidence: 84%
“…Here, we have shown that increased RT variability is associated with self-reports of greater off-task attention at both intra-and interindividual levels, yet decreased RT variability and off-task self-reports have separately been previously associated with increased DMN activity (9,10,12,19,20). To evaluate each of those relationships in our paradigm, we extracted mean activity level (percent signal change, %SC) in 30-s prerating periods from the DMN, defined from a network atlas developed in an independent, large cohort of subjects, and including gray matter in the medial prefrontal cortex, posterior cingulate cortex, lateral parietal areas, portions of the temporal lobe, and cerebellar A B C components (Fig.…”
Section: Dmn Fluctuations Reflect Both Self-reported Attention and Bementioning
confidence: 72%
See 2 more Smart Citations
“…Several recent studies found that activity in the DMN is inversely related to measures of behavioral variability (i.e., poorer task performance) [41][42][43]. For example, in a fingertapping task, increased tap variability was associated with reduced DMN activity [43] even though behavioral variability is consistently associated with mind wandering [44,45].…”
Section: Implications Of the Modelmentioning
confidence: 99%